H Hubungan NF-kB Pada Diabetes Dislipidemia : Literature Review: Hubungan NF-kB Pada Diabetes Dislipidemia : Literature Review - Nungky Yulia; Saftia Aryzki; Muhamma Rizki Ikhsan (LPPM Universitas Sari Mulia, 2022)
Background: The NF-kB cytokine that produced can induces an acute phase called low-grade inflammation which is part of the activity of the innate immune system. this is associated with the pathogenesis of type 2 DM, then complications occur, namely dyslipidemia and atherosclerosis. Proinflammatory cytokines that act as stress inducers in endoplasm which can increase insulin metabolism and in type 2 diabetes, which is characterized by decreased insulin production and insulin resistance.Objective: This study aimed to identified and analyzed the relationship of NF-kB with diabetic dyslipidemia.Methods: Assessment of criteria in this literature review study using The JBI Critical Appraisal Tools to assessed the risk of bias in the study with type of study was Randomized Controlled Trials. this study conducted by using data on article from data base such as PubMed, Elsevier, google schoolar, etc.Results: NF-kB had Relationship with diabetic dyslipidemia with the results of P value> 0.005 and significance value of serum TNF-a level (p = 0.002), serum IL-6 level (p = 0.067) in diabetes induced dyslipidemia. Diabetic dyslipidemia that analyzed with insertion genotype showed increased in proinflammatory cytokine expression and activity of NF-kB.Conclusion: Most research results stated that there was a relationship between NF-kB with diabetic dyslipidemia. This was proven with high serum and TNF-a levels NF-kb, that played a role in complications related to diabetes mellitus through its role in inducing inflammation.